2021
DOI: 10.1177/07435584211062112
|View full text |Cite
|
Sign up to set email alerts
|

Critical Reflection and Cognitive Empowerment among Youth Involved in Community Organizing

Abstract: Through youth organizing initiatives, young people conduct research into social issues and build power to address these issues. This study examines the developmental interplay between the cognitive components of two of the most influential civic developmental constructs—critical consciousness and psychological empowerment—through analysis of interviews with 19 current and former participants in a youth organizing initiative in San Bernardino, CA, all of whom identify as Latinx. Most participants clearly articu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…T A B L E 3 One-way ANOVA of socio-political control, critical thinking, and ethnic identity according to membership in a migrant community-based organization. Regarding the first objective of the study, the results showed that the means obtained in the dimensions of socio-political control, as well as in ethnic identity, were significantly higher in MCBO members than in nonmembers, as supported by the previous literature (Christens et al, 2021;Gutierrez, 1988;Itzhaky & York, 2000;Peucker, 2020;Speer et al, 2001;Zimmerman, 1990). Moreover, we found that migrant…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…T A B L E 3 One-way ANOVA of socio-political control, critical thinking, and ethnic identity according to membership in a migrant community-based organization. Regarding the first objective of the study, the results showed that the means obtained in the dimensions of socio-political control, as well as in ethnic identity, were significantly higher in MCBO members than in nonmembers, as supported by the previous literature (Christens et al, 2021;Gutierrez, 1988;Itzhaky & York, 2000;Peucker, 2020;Speer et al, 2001;Zimmerman, 1990). Moreover, we found that migrant…”
Section: Discussionsupporting
confidence: 80%
“…Regarding the first objective of the study, the results showed that the means obtained in the dimensions of socio‐political control, as well as in ethnic identity, were significantly higher in MCBO members than in nonmembers, as supported by the previous literature (Christens et al, 2021; Gutierrez, 1988; Itzhaky & York, 2000; Marzana et al, 2020; Peucker, 2020; Speer et al, 2001; Zimmerman, 1990). Moreover, we found that migrant members of an MCBO reported higher levels of critical thinking, indicating the relationships found by others both among the general population and ethnic minorities (Budziszewska & Głód, 2021; Christens et al, 2021; Lardier et al, 2021; Petrovčič & Petrič, 2014; Speer et al, 2013). These results suggested that participation in community settings such as MCBOs—where migrants can find a group of people with whom they can share the hardships of migration, as well as those of living in the new society, and with whom they can remember their traditions and culture—can be truly empowering (Maton, 2008).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The association between racism and mental health may be attenuated for youth who engage in more critical action, in combination with greater feelings of critical agency or more critical reflection of oppression. Understanding structural oppression and feeling empowered to seek social change may give adolescents a deeper sense of purpose as they engage in critical action that supports their mental health and well-being, even throughout the long process of social justice change work [41]. When youth who have deeper critical reflection experience racism, they may attribute the racism to systems and structures and may not internalize racism as a reflection of their individual or racial group's worth [28].…”
Section: Critical Consciousness For Coping With Racismmentioning
confidence: 99%